Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.2147/copd.s118106
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for FEV<sub>1</sub> decline in mild COPD and high-risk populations

Abstract: BackgroundEarly diagnosis of COPD is often not achieved due to limited recognition and limited access to the pulmonary function test. Our hypothesis was that lung function decline may be different between populations with mild COPD and those who are at high risk and do not receive treatment.Patients and methodsSubjects with mild COPD and those from a high-risk COPD population were recruited from a community-based COPD epidemiological study after obtaining consent. Baseline clinical characteristics, symptom que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 42 publications
0
23
1
Order By: Relevance
“…Despite the overall negative outcome, the subgroup analyses revealed that those with less advanced lung disease appeared to obtain the benefit of reducing FEV 1 decline, supporting the relevance of early treatment . This idea is compelling, as later studies found that the FEV 1 decline may be more rapid during early stages . Therefore, if our objective is to alter the natural course of the disease by reducing the rate of FEV 1 decline, then the approach should comprise double bronchodilator treatment during the early stages of disease to slow progression, followed by either single or double bronchodilator therapy during more advanced stages according to the need for symptom control.…”
Section: Step Up From Single To Double Bronchodilationmentioning
confidence: 90%
“…Despite the overall negative outcome, the subgroup analyses revealed that those with less advanced lung disease appeared to obtain the benefit of reducing FEV 1 decline, supporting the relevance of early treatment . This idea is compelling, as later studies found that the FEV 1 decline may be more rapid during early stages . Therefore, if our objective is to alter the natural course of the disease by reducing the rate of FEV 1 decline, then the approach should comprise double bronchodilator treatment during the early stages of disease to slow progression, followed by either single or double bronchodilator therapy during more advanced stages according to the need for symptom control.…”
Section: Step Up From Single To Double Bronchodilationmentioning
confidence: 90%
“…The literature search identified several papers reporting data for disease progression in patients with mild COPD or smokers with abnormal lung function (Fig. 1) [29, 5860]. There is evidence that patients with mild COPD have an accelerated FEV 1 decline compared with controls without COPD (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that patients with mild COPD have an accelerated FEV 1 decline compared with controls without COPD (Fig. 1) [29, 58]) and GOLD stages 2–4 [29], which is more prominent in patients with greater symptoms [29, 59]. In contrast, one study reported that male heavy smokers with FEV 1 /FVC > 0.7 had a more rapid rate of decline irrespective of whether they were above or below the lower limit of normal (LLN), compared with individuals with FEV 1 /FVC < 0.7 and < LLN, (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of decline in FEV1 from a study in Japan was 32 ml/year, and in the Lung Health Study, the declining was 45 ml/year. [3] However, declining lung function within 1 year among Indonesian patients with COPD remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%